Learning to write a linguistic autobiography. An example of reflective and metacognitive writing in teacher training - Casas-Deseures, Mariona (2020)
This paper presents an experience of teaching innovation on academic writing carried out in the subject Expression and Communication Techniques of the 1st year of the Teacher Training degrees at the Universitat de Vic-Universitat Central de Catalunya (UVic-UCC). This is a core subject (6 ECTS) which aims to provide students (future teachers) with the necessary tools to communicate effectively in the academic field. The experience consists in the implementation of a reflective writing project that proposes students to write their own linguistic autobiography, a reflective genre whose objective is to become aware of the learning process and the use of the different languages throughout life. The project is developed throughout the semester, following the three stages of the writing process (planning, composing and review) and sequences all the steps students have to take in order to write their linguistic autobiography. This educational experience highlights the epistemic function of writing, essential to develop students’ metacognitive ability, and confirms the need to intensify the teaching of academic writing at the university.